ORAL HEALTH KNOWLEDGE, ATTITUDE, AND PRACTICES AMONG TYPE-2 DIABETICS: A CROSS-SECTIONAL STUDY - Ravi Anjan; Upasana Sethi Ahuja; Sourav Kumar Pradhan; Medha; Biduyat Kumar Saikia; Akansha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Diabetes mellitus represents a growing global health crisis, with its incidence rising rapidly worldwide. It is characterized by the body's impaired ability to effectively utilize insulin, often associated with lifestyle factors such as obesity and sedentary behaviour. Despite the significant risks, many individuals with diabetes remain unaware of the oral health challenges related to their condition and the importance of preventive care. This study underscores the urgent need to enhance awareness and understanding of oral health among diabetic patients. Maintaining good oral hygiene is crucial in preventing and managing gingival and periodontal infections, which tend to be more severe in individuals with diabetes.Aims & Objectives: The primary aim of this study is to assess the oral health status of individuals diagnosed with Type 2 diabetes mellitus and evaluate their knowledge, attitudes, and practices concerning oral health.Methodology: A cross-sectional study design was employed to investigate the oral health status and survey the knowledge, attitudes, and practices of individuals with Type 2 diabetes mellitus. The World Health Organization's Oral Health Assessment form was utilized, complemented by a self-developed, close-ended, pre-validated questionnaire. Statistical analysis was conducted to interpret the collected data.Results: The results indicate a significant deficiency in knowledge among diabetic patients regarding the oral health complications associated with their condition, as well as the importance of proper preventive care. This highlights the critical need for educational initiatives aimed at improving the understanding and attitudes of diabetic patients towards the oral health risks linked to diabetes. Conclusion: Overall, individuals with diabetes exhibit limited awareness and inadequate practices concerning oral health. It is essential to educate diabetic patients about their heightened risk for oral health issues, encourage better oral health practices, and ensure they have access to appropriate dental care.